2021
DOI: 10.18502/ijrm.v19i3.8570
|View full text |Cite
|
Sign up to set email alerts
|

The exact synchronization timing between the cleavage embryo stage and duration of progesterone therapy-improved pregnancy rates in frozen embryo transfer cycles: A cross-sectional study

Abstract: Background: Synchronization between the embryonic stage and the uterine endometrial lining is important in the outcomes of the vitrified-warmed embryo transfer (ET) cycles. Objective: The aim was to investigate the effect of the exact synchronization between the cleavage stage of embryos and the duration of progesterone administration on the improvement of clinical outcomes in frozen embryo transfer (FET) cycles. Materials and Methods: 312 FET cycles were categorized into two groups: (A) day- 3 ET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, the optimal duration of WOI is restrictedly short and only continues about 24-48 hours in human (Galliano et al 2015). Profound evidences demonstrated that blastocyst-endometrial asynchrony would result in defective implantation or implantation failure (Ming et al 2012;Healy et al 2017;Omidi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the optimal duration of WOI is restrictedly short and only continues about 24-48 hours in human (Galliano et al 2015). Profound evidences demonstrated that blastocyst-endometrial asynchrony would result in defective implantation or implantation failure (Ming et al 2012;Healy et al 2017;Omidi et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, the optimal duration of WOI is restrictedly short and only continues about 24-48 hours in human (Galliano et al 2015). Profound evidences demonstrated that blastocyst-endometrial asynchrony would result in defective implantation or implantation failure (Ming et al 2012; Healy et al 2017; Omidi et al 2021). Unsatisfactory pregnancy outcomes among RIF patients might be ascribed to the displacement of the WOI, in which embryos were transferred to the non-receptive endometrium at conventional timing (Hashimoto et al 2017).…”
Section: Introductionmentioning
confidence: 99%